Warna Hijau di dalam al-Quran dan Peranannya Sebagai Elemen Nonfarmakologi Bagi Mengurangkan Kadar Kebimbangan (Anxiety): The Colour Green in the Qurʾān: A Non-Pharmacological Approach to Alleviating Anxiety - Norwardatun Mohamed Razali; Nathratul Ayeshah Zulkifli (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
Colour is a fundamental element in human life, and the Qurʾān frequently highlights specific colours to convey distinct meanings and contexts. Among these, green receives particular emphasis, suggesting symbolic and psychological significance. Beyond its scriptural usage, green is recognised in colour therapy as a non-pharmacological means of reducing anxiety. This study aims to identify and analyse Quranic verses that mention the colour green, and to examine their potential connection to its therapeutic application in alleviating anxiety. Employing an inductive method, the researcher compiled and examined the Quranic verses explicitly referencing the colour green. Preliminary findings reveal nine such verses, presenting green as indicative of plant life in this world and symbolising the blessings awaiting believers in the hereafter. From a mental health perspective, research suggests that exposure to green can help reduce anxiety levels. Thus, the Quranic emphasis on green appears to parallel the calming and restorative influence that this colour exerts on human emotions. In essence, the scriptural selection and portrayal of green harmonise with its soothing and comforting effects, offering valuable insights for both spiritual reflection and therapeutic practice.